Explaining Episodes of Growth Accelerations, Decelerations, and Collapses in Western Africa - Salinas, Gonzalo (IMF Working Papers; Working Paper, 2008)
The growth literature has had problems explaining the "sub-Saharan African growth dummy" in cross-country regressions. Instead of taking the usual approach of focusing on long-run growth and assuming that sub-Saharan countries have homogenous parameters in growth regressions, we concentrate our analysis on episodes of growth turnarounds (identifying growth accelerations, decelerations, and collapses) and use only West African countries in our sample. The driving force of growth turnarounds are estimated by analyzing external shocks, political and institutional changes, economic reforms, and indicators particularly relevant to the region. Using probits for a group of 22 Western African economies for the period 1960-2006, we find that growth accelerations are most clearly associated with external shocks, economic liberalization, political stability, and closeness to the coast; decelerations occurred during short-lived regimes and when corruption indices weakened; and collapses are linked to external shocks, falling domestic credit, and proximity to the coast. We then identify policy implications.